THE FIRST EXPERIENCE OF SUCCESSFUL SMALL BOWEL TRANSPLANTATION IN THE SKLIFOSOVSKY RESEARCH INSTITUTE FOR EMERGENCY MEDICINE - M. Sh. Khubutia; P. A. Yartsev; V. A. Gulyaev; A. V. Grishin; S. A. Tarasov; N. N. Sheptak; M. N. Drayer; I. V. Aleksandrova; V. V. Kiselev; A. A. Ryk; A. V. Vodiasov; O. N. Rzhevskaya; et al. (Неотложная медицинская помощь, 2016)
ABSTRACT. The paper describes the first experience of successful small bowel transplantation in the Sklifosovsky Research Institute for Emergency Medicine. It contains a brief review of literature on essential aspects of small bowel transplantation, presents the donor’s case history, specific features of anesthesia, surgical procedure, and postoperative course, including the immunosuppression scheme, diagnosis and treatment of evolved complications. The paper provides in-detail results of morphological control over rejection development, presents the data of ultrasonographic observation of the changes in the transplanted intestine in the course of its adaptation to new requirements, covers the tactics of parenteral and enteral nutrition.